1989
DOI: 10.1111/j.1540-8159.1989.tb02676.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Consequences of Permanent Pacemaker Therapy in Patients Under the Age of Retirement

Abstract: During a 5-year period, 81 patients ages 20 to 60 years old had implantation of a permanent cardiac pacemaker at the University Hospital, Odense. At follow-up, during 1985, the 73 survivors received a semi-structured questionnaire regarding subjective consequences of pacemaker therapy, and 72 people (98.6%) agreed to participate. The mean pacing period (range) was 33.8 (11-72) months. Surgical intervention was required in 14 patients (19.4%) during follow-up. Regarding all symptoms 67 patients (93.1%) perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…While chronic indolent infection and regional pain syndromes are often considered and treated, generator movement within the pocket is often overlooked. Prior studies have shown that almost a quarter of patients undergoing CIED implantation report pain or discomfort with movement of the generator in the pocket [3]. Shoulder pain and limitation of movement ipsilateral to the CIED site are also common [4].…”
Section: Discussionmentioning
confidence: 99%
“…While chronic indolent infection and regional pain syndromes are often considered and treated, generator movement within the pocket is often overlooked. Prior studies have shown that almost a quarter of patients undergoing CIED implantation report pain or discomfort with movement of the generator in the pocket [3]. Shoulder pain and limitation of movement ipsilateral to the CIED site are also common [4].…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Accordingly, sexual activity often decreases after ICD implantation. [62][63][64] The sexual partner is not believed to be at risk from defibrillation if the ICD discharges during sexual activity. 61,64 Stress testing may provide reassurance to the patient and spouse or partner that sexual activity is unlikely to precipitate or exacerbate arrhythmia.…”
Section: Arrhythmias Pacemakers and Icdsmentioning
confidence: 99%
“…The quality of life of pacemaker patients has been investigated by several authors using different criteria and instruments. After a mean pacing period of 34 months, 43% of the patients under the age of retirement showed an improvement of quality of life, 42% stayed unchanged and 14% felt a deterioration (self-developed questionnaire) (23). In a six-month study an overall of 80% of unselected pacemaker patients showed an improvement as rated by a Foulds' Personal Disturbance Scale (33).…”
Section: The Follow-up Periodmentioning
confidence: 99%